(untitled) (MAUSAM, 1984)
This is the study of a cyclone over the Indian seas in 1981 using enhanced advanced yery High Resolution Radiometer (AVHRR) pictures received at New Delhi. We note that the area bounded by the temperature contour of -65 deg. C defines the Central Dense Overcast (CDO). The size of the CDO was seen to increase with the intensity of the storm. This could be used as a parameter to forecast intensification. Even though the storm attained the intensity of a severe cyclonic storm with a core of hurricane winds, there was no ‘eye’. Thus a severe cyclonic storm with a core of hurricane winds may exist without an ‘eye’ in satellite pictures. With the advent of INSAT more frequent pictures at half hourly intervals will become available when more light can be thrown on the ‘eye’ characteristics.